2022
DOI: 10.1177/23998083221138832
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating networks in semantic understanding of streetscapes: Contextualising active mobility decisions

Abstract: Planning for active mobility satisfies many fundamental tenets of good urban design and planning. However, planning for active mobility is a complex endeavour due to numerous local, place-based factors that influence active mobility decisions. Recent advancements in urban data research have demonstrated the effectiveness of deep learning methods in evaluating active mobility potential for urban environments. At present, the incorporation of semantic information from deep learning models and street view imagery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…At the district (WETDZ) level, we assessed the number of accessible cultural and sports facilities within 1,000 m and 2,000 m based on road network. This approach helps to illustrate the possible combinations of origin–destination traffic between residential areas and service facilities [ 39 ] as well as to map the overall coverage of facilities by the whole network, thereby creating a schematic diagram of the cultural and sports facilities’ accessibility in the WETDZ in a spatially explicit way.…”
Section: Methodsmentioning
confidence: 99%
“…At the district (WETDZ) level, we assessed the number of accessible cultural and sports facilities within 1,000 m and 2,000 m based on road network. This approach helps to illustrate the possible combinations of origin–destination traffic between residential areas and service facilities [ 39 ] as well as to map the overall coverage of facilities by the whole network, thereby creating a schematic diagram of the cultural and sports facilities’ accessibility in the WETDZ in a spatially explicit way.…”
Section: Methodsmentioning
confidence: 99%
“…Advancements in urban data research have demonstrated the effectiveness of deep learning methods in evaluating active mobility potential for urban environments. Yap et al [25] integrated street view imagery and urban networks to evaluate active mobility, using deep learning to assess traffic environment factors impacting subjective decisions. Unlike traditional GPS resources, Chen and Yang [26] combined social media signals with pedestrian simulation technologies in historic neighborhoods, addressing conflicts between tourists and locals and enhancing urban planning.…”
Section: Transportation and Contextmentioning
confidence: 99%
“…Enhances active mobility planning using deep learning DeepLabV3 segmentation trained on a WideResNet-38 model analyzing street imagery. [25] Uses big data, pedestrian simulation, and AnyLogic to identify facility gaps and traffic issues.…”
Section: Decision and Simulationmentioning
confidence: 99%
“…Network population estimates can also help evaluate the accessibility of public facilities, such as schools, hospitals, or parks, empowering planners to pinpoint underserved areas and prioritise infrastructure investments [39][40][41] . Street view indicators along network edges are crucial for modeling pedestrian-friendly urban environments and suggesting improvements to promote walking, cycling, and other active transportation modes [42][43][44][45] In emergency planning, identifying critical nodes and links can inform strategies to enhance city resilience against various shocks and stresses, including climate change, natural disasters, or economic fluctuations. Lastly, building morphology information along networks plays a vital role in energy-based modeling and carbon forecasting for urban areas, providing insights into the implications of urban growth for social, economic, and environmental outcomes 19,46 .…”
Section: Background and Summarymentioning
confidence: 99%